2017
DOI: 10.1002/psc.2979
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity inhibition by overlapping synthetic peptides derived from the gH/gL heterodimer of herpes simplex virus type 1

Abstract: Herpes simplex virus (HSV) is a human pathogen that infects epithelial cells. The cutaneous lesions, caused by the virus, spread to the nervous system creating several complications. Fusion of host membranes with the viral envelope is mandatory and mediated by a group of glycoproteins conserved in all Herpesviridae subfamilies, such as the glycoproteins B (gB), H (gH), L (gL) and D (gD). We investigated the inhibitory activity mediated by synthetic overlapping peptides spanning the entire ectodomains of gH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…The peptide gH493-512 was used as a positive control in co-treatment and virus pre-treatment assays, while dextran sulphate and acyclovir were used for cell-treatment and post-treatment assay, respectively [ 57 ]. In order to evaluate the antiviral activity of the extracts on HSV, four different assays were performed [ 56 , 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…The peptide gH493-512 was used as a positive control in co-treatment and virus pre-treatment assays, while dextran sulphate and acyclovir were used for cell-treatment and post-treatment assay, respectively [ 57 ]. In order to evaluate the antiviral activity of the extracts on HSV, four different assays were performed [ 56 , 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it is also well known that thiol groups are present in the cysteine amino acid, abundant in many spike glycoproteins of viruses. For example, in the case of HSV-1 the B Glycoprotein, essential for the attachment and fusion to the host cell (Cooper and Heldwein, 2015;Franci et al, 2017;Stelitano et al, 2019) has a cysteine residue (Laquerre et al, 1998) that can certainly repel with thiols, which can be formed on the MoS 2 flake edge, where the abundant presence of sulfur atoms in solution can lead to the formation of −SH groups with the capture of an H + ion.…”
Section: Virus Pre-treatment Experimentsmentioning
confidence: 99%
“…Several studies reported antimicrobial resistance (AMR) among Staphylococcus species . Among these, The National Surveillance Study (ARMOR) has monitored eye infections since 2009 for bacterial species resistance profiles [ 13 , 14 ]. In particular, MR- Staphylococcus strains showed not only β-lactam antibiotic resistance but also a resistance profile to other antimicrobial agents commonly used in the treatment of ocular infections The improper, excessive or empirical use of antimicrobial agents increased the resistance profile pattern.…”
Section: Introductionmentioning
confidence: 99%